Dental alginate impression waste as additional fertiliser for plant yields and soil quality - Frahdian, Tommy; Hasratiningsih, Zulia; Karlina, Elin; Herdiyantoro, Diyan; Takarini, Veni (Padjadjaran Journal of Dentistry, 2018)
Introduction: Dental alginate impression material is the most common material used in dentistry. However, dental alginate waste (DAW) is one of the causes of the increasing number of dentistry and medicinal wastes. This research was aimed to discover the effect of dental alginate impression waste as additional fertiliser on the plant yields by determining the weight of cauliflower crop, and towards the quality of soil by determining the soil pH (UltisolÂ® Jatinangor). Methods: The experiment was using a randomised block design with 4 treatments and 7 times replications. The treatment consisted of A0 (0% DAW as control), A1 (0.01% DAW), A2 (0.1% DAW), and A3 (1% DAW). Results: The weight of cauliflower after addition of DAW in group A0 was 72.78; A1 was 139.82); A2 was 130.69; and A3 was 60.72). While the pH soil in group A0 was 5.92; A1 was 6.07; A2 was 6.02; and A3 was 6.26. The treatment in the A1 and A2 groups were found as the significant doses that able to increase the cauliflower weight for consecutively 1.92 times and 1.80 times compared to the control group, while on the soil quality improvement (soil pH), the addition of DAW was not significantly affected. Conclusion: It can be concluded that the addition of dental alginate waste at the dose of 0.01% and 0.1% increased the weight of cauliflower, but has no significant effect on the soil quality.